CRA Grade Inflation - Ph.D. Kenneth H. Thomas (Levy Economics Institute of Bard College, 2000)
Community Reinvestment Act of 1977 (CRA) ratings and performance evaluations are the only bank and thrift exam findings disclosed by financial institution regulators. Inflation of CRA ratings has been alleged by community activists for two decades, but there has been no quantification or empirical investigation of grade inflation. Using a unique grade inflation methodology on actual ratings and evaluation data for 1,407 small banks and thrifts under the revised CRA regulations, this paper concludes that nearly half of all CRA ratings are inflated. Results are presented for the four federal bank and thrift regulators and their 31 regional offices. These findings are consistent with the "Friendly Regulator Hypothesis."
Keywords: 330